PENGARUH TATA KELOLA PERUSAHAAN DAN TRANSFER HUBUNGAN ISTIMEWA TERHADAP TARIF PAJAK EFEKTIF PERUSAHAAN - Yudawirawan, Moh. Yuddy; Yanuar, Yayan; Hamdy, Syaibatul (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to analyze the effect of corporate governance and transfer of special relationships to effective tax rates. This method uses quantitative descriptive. This population is 89 companies and uses various industrial manufacturing sub-sector companies and consumer goods industries, with a sample of 52 with purposive sampling in sampling techniques. The data analysis technique uses SPSS 24 with descriptive statistical tests, classic assumption tests, partial tests and simultaneous tests using multiple linear regression methods. The results show simultaneously that corporate governance variables and transfer of special relationships have a significant effect on effective tax rates. This is proven by the significance value of 0.007 less than 0.05